Analisis Minat Belajar Siswa pada Pembelajaran IPS secara Daring di Masa Pandemi Covid-19 - Nurjanah, Eka; Saputra, Yudha Munajat; Karlina, Dety Amelia (Jurnal Pena Ilmiah, 2021)
TheÂ  purpose of this study was to determine student interest in learning, factors that influence student interest in learning and teacher efforts in fostering student interest in social studies learning in online learning. The research method used is qualitative with a descriptive research design. The results of the study found that students were interested in online social studies learning this was based on the pleasure, interest, acceptance and involvement of students in the learning process. The factors that influence student learning interest are students who enjoy learning social studies, an environment that supports students' learning such as parents and teachers. In addition, difficult material, inadequate quota/network and not all students have their own cellphones hinder students' interest in learning online. The teacher makes efforts to foster student interest in learning by paying attention to social studies material that is adapted to the media, providing material reinforcement, using assignment methods and presenting material from videos, PPT, modules or worksheets. In addition, rewards in the form of a thumb and star symbol are given to students to be motivated to always follow online learning. This has an impact on the online social studies learning process, students are more active in participating in learning and doing assignments.